2008
DOI: 10.1093/hmg/ddn020
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genetic analysis of the platelet activating factor acetylhydrolase (PLA2G7) gene and cardiovascular disease in case–control and family datasets

Abstract: Platelet-activating factor acetylhydrolase (PLA2G7) is a potent pro- and anti-inflammatory molecule that has been implicated in multiple inflammatory disease processes, including cardiovascular disease. The goal of this study was to investigate the genetic effects of PLA2G7 on coronary artery disease (CAD) risk in two large, independent datasets with CAD. Using a haplotype tagging (ht) approach, 19 ht single nucleotide polymorphisms (SNPs) were genotyped in CATHGEN case-control samples (cases = 806 and control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
76
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 49 publications
5
76
4
Order By: Relevance
“…Also, sutton et al, 26 reported that 379V polymorphism was more prevalent among MI patients than controls with a significant difference (p=0.002) which was against our results. this dissimilarity in results may be due to differences in ethnic groups, sample size and selection criteria of patients and controls.…”
Section: Discussioncontrasting
confidence: 99%
“…Also, sutton et al, 26 reported that 379V polymorphism was more prevalent among MI patients than controls with a significant difference (p=0.002) which was against our results. this dissimilarity in results may be due to differences in ethnic groups, sample size and selection criteria of patients and controls.…”
Section: Discussioncontrasting
confidence: 99%
“…The association of R92H with cardiovascular disease is also contradictory. Sutton et al (8) reported that the R92H polymorphism was significantly associated with the risk of CHD, with the R92H variant allele observed more frequently in the experiment group compared to the control group. Zheng et al (14) identified the significant association of the R92H variant with premature myocardial infarction in the Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…V279F in exon 9 of the PAF-AH gene is associated with coronary artery disease and carotid atherosclerosis in the Japanese population. R92H in exon 4 is associated with coronary artery disease in the USA (8). According to this information, we hypothesized that the genetic variants in PAF-AH may have a critical role in the susceptibility to ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…But in other studies, such as Wang et al (2010), did not find association between V279F and CHD. Views toward roles that R92H and I198T mutations play in the development of CHD have also been controversial (Hou et al 2009;Sutton et al 2008;Wang et al 2010). Study type, ethnic differences, inclusion criteria, and other factors may be the reasons for these diversities of conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the biological function related to the same variant in PLA2G7 SNPs remain quite contrary. For example, Sutton et al found that R92H was the most significantly associated SNP, while no difference was found between case group and control group with I198T mutations (Sutton et al 2008). Xu et al pointed out that R92H was protective factor against CHD in females (Xu et al 2013).…”
Section: Introductionmentioning
confidence: 99%